1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cruzipain, the Major Cysteine Proteinase of Trypanosoma cruzi, is Associated with Enhanced Metacyclogenesis

Abstract: Cruzipain, the major cysteine proteinase of Trypanosoma cruzi has been proposed as a target for chemotherapy against Chagas' disease. To investigate the role of cruzipain we transfected 7: cruzi epimastigotes with a recombinant cosmid containing approximately 20 tandenily repeated cruzipain genes. Transformed cells had multiple episomal copies of the vector and exhibited considerable overexpression of cruzipain activity. The upregulation was maintained throughout the parasite life-cycle, and electrophoretic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 33 publications
5
53
0
1
Order By: Relevance
“…The process, therefore, requires fast and extensive protein degradation and recycling of building blocks for the synthesis of new macromolecules. Initial studies suggested that cruzipain, the most abundant lysosomal/reservosomal cysteine peptidase of T. cruzi belonging to the CA clan (21) of proteases, is critical for the differentiation as the cell-permeable cruzipain inhibitors effectively inhibited the process (19,51), whereas overexpression of this enzyme is associated with enhanced metacyclogenesis (52). Our results clearly demonstrate that autophagy is also involved in cell remodeling most probably by delivering large parts of the cytoplasm and organelles to lysosomes/reservosomes.…”
Section: Discussionsupporting
confidence: 53%
“…The process, therefore, requires fast and extensive protein degradation and recycling of building blocks for the synthesis of new macromolecules. Initial studies suggested that cruzipain, the most abundant lysosomal/reservosomal cysteine peptidase of T. cruzi belonging to the CA clan (21) of proteases, is critical for the differentiation as the cell-permeable cruzipain inhibitors effectively inhibited the process (19,51), whereas overexpression of this enzyme is associated with enhanced metacyclogenesis (52). Our results clearly demonstrate that autophagy is also involved in cell remodeling most probably by delivering large parts of the cytoplasm and organelles to lysosomes/reservosomes.…”
Section: Discussionsupporting
confidence: 53%
“…1C). These values are comparable to those from other studies using pTEX or pTEX-derived vectors to overexpress proteins in the cytosol (78,79), mitochondria (80), glycosomes (81), endosomal/lysosomal system and reservosomes (75,82), ER (68), flagellar pocket (83), or plasma membrane (69,(84)(85)(86) of T. cruzi. The protein was stable, with no indication of a C-terminal proteolytic cleavage event observed when expressed in L. tarentolae (21), and it appeared to be inserted into the rER and N-glycosylated normally (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Overexpression of superoxide dismutase resulted in increased sensitivity to the trypanocidal agents crystal violet and benzidazole (39), although overexpression of cruzipain, the major cysteine proteinase of T. cruzi, was associated with enhanced metacyclogenesis (40). We found that overexpression of TcPI-PLC resulted in an increased rate of differentiation of trypomastrigotes into amastigotes (Figs.…”
Section: Fig 5 Probability Of Differentiating As a Function Of Treamentioning
confidence: 62%